ChemInform Abstract: Tomensides A—D, New Antiproliferative Phenylpropanoid Sucrose Esters from Prunus tomentosa Leaves. Issue 40 (30th September 2014) - Zhao, Wei; Huang, Xiao‐Xiao; Yu, Li‐Hong; Liu, Qing‐Bo; Li, Ling‐Zhi; Sun, Qian; Song, Shao‐Jiang
Abstract The 3‐phenylpropanoid‐triacetyl sucrose esters, tomensides A‐D (I), are isolated along with three known analogs from the leaves of Prunus tomentosa.